A romance of two worlds - Corelli, Marie, 1855-1924 (Edinburgh critical editions of nineteenth-century texts., 2019)
Marie Corelli's A Romance of Two Worlds is regarded as one of the most culturally important Victorian bestsellers. This critical edition offers instructive access to this multifaceted but still largely underappreciated novel.